2018
DOI: 10.1097/md.0000000000010063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the short-term outcomes between delta-shaped anastomosis and conventional Billroth I anastomosis after laparoscopic distal gastrectomy

Abstract: Background:The conventional Billroth I anastomosis (cBIA) after laparoscopic distal gastrectomy (LDG) is performed through circular staple extracorporeally. Now, delta-shaped anastomosis (DA), which is performed using a linear stapler intracorporeally, becomes popular. We conducted a meta-analysis to compare the effectiveness and safety between the 2 techniques.Methods:A systematic literature search was performed using PubMed, Ovid, and the Cochrane Library Central. Participants of any age and sex, who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…Many reports have evaluated the surgical outcomes and safety of ICBI versus ECBI [6781316171819202122]. A recent meta-analysis [910] of more than 10 articles revealed that ICBI was feasible and safe. Although many reports [56789101316171819202122] have shown that total laparoscopic ECBI anastomosis is feasible and safe, some surgeons still avoid the procedure and hesitate to perform ICBI anastomosis using linear staplers due to concerns about anastomosis problems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many reports have evaluated the surgical outcomes and safety of ICBI versus ECBI [6781316171819202122]. A recent meta-analysis [910] of more than 10 articles revealed that ICBI was feasible and safe. Although many reports [56789101316171819202122] have shown that total laparoscopic ECBI anastomosis is feasible and safe, some surgeons still avoid the procedure and hesitate to perform ICBI anastomosis using linear staplers due to concerns about anastomosis problems.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis [910] of more than 10 articles revealed that ICBI was feasible and safe. Although many reports [56789101316171819202122] have shown that total laparoscopic ECBI anastomosis is feasible and safe, some surgeons still avoid the procedure and hesitate to perform ICBI anastomosis using linear staplers due to concerns about anastomosis problems. Considering that surgeons currently perform laparoscopic gastrectomy after adaptation for open gastrectomy, it is anticipated that surgeons would be comfortable performing ECBI anastomosis under direct vision using the circular stapler, similar to open surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that DA resulted in less blood loss and faster recovery than B-I, especially in obese patients. However, no difference was found in the surgical outcomes (operative time, number of harvested lymph nodes, and proximal margin) and postoperative complications (anastomotic leakage, stricture, hemorrhage, and wound complications) [22][23][24] (Table 1). However, some researchers have indicated that DA may affect the blood supply during cutting and result in an increased risk of anastomosis-related complications [25] .…”
Section: B-i Reconstructionmentioning
confidence: 97%